Team resilience emergence: Perspectives and experiences of military personnel selected for elite military training - Chapman, Michael; Temby, P.; Crane, M.; Ntoumanis, Nikos; Quested, Eleanor; Thogersen-Ntoumani, Cecilie; Parker, Sharon; Ducker, Kagan; Peeling, P.; Gucciardi, Daniel (WILEY, 2021)
We conducted a longitudinal (3-month) qualitative study to examine elite military personnel's (N = 32) experiences and perspectives of team resilience emergence following two team-oriented training courses within an 18-month high-stakes training programme where personnel are required to operate in newly formed tactical teams for extended periods. Our thematically informed interpretations of the participants’ subjective experiences of reality were constructed according to five key themes: (i) adversity is an enduring, shared experience of an event; (ii) individuals recognise adversity through physiological and/or behavioural states; (iii) social resources bind together individual self-regulatory capacities when confronted with adversity to support team functioning; (iv) shared experiences of adversity and collective structures strengthen social bonds and mental models needed for resilience emergence; and (v) behavioural processes and shared states are how collectives turn individual and team capacities into performance under adversity. These findings provide novel insights that supplement our current understanding of team resilience emergence, including the varying means by which adversity may be collectively experienced, synergies between specific forms of adversity and resilience processes or protective factors, and the unique influence of performance context (e.g., task type).